2002
DOI: 10.1098/rspb.2002.2114
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for major histocompatibility complex–allele–specific resistance to a bacterial infection

Abstract: The extreme polymorphism found at some major histocompatibility complex (MHC) loci is believed to be maintained by balancing selection caused by infectious pathogens. Experimental support for this is inconclusive. We have studied the interaction between certain MHC alleles and the bacterium Aeromonas salmonicida, which causes the severe disease furunculosis, in Atlantic salmon (Salmo salar L.). We designed full-sibling broods consisting of combinations of homozygote and heterozygote genotypes with respect to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
114
0
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(121 citation statements)
references
References 25 publications
5
114
0
2
Order By: Relevance
“…Langefors et al (2001) found an association between certain MHC class IIb alleles and resistance to the bacterial pathogen Aeromonas salmonicida in experimentally challenged Atlantic salmon (Salmo salar). Lohm et al (2002) subsequently selectively mated the uninfected siblings of these fish, combining high-and low-resistance alleles within full-sibling families, thereby controlling for the potentially confounding effects of family. This study revealed a codominant pattern of resistance/susceptibility to A. salmonicida infection.…”
Section: Evolutionary Ecology Of the Mhcmentioning
confidence: 99%
“…Langefors et al (2001) found an association between certain MHC class IIb alleles and resistance to the bacterial pathogen Aeromonas salmonicida in experimentally challenged Atlantic salmon (Salmo salar). Lohm et al (2002) subsequently selectively mated the uninfected siblings of these fish, combining high-and low-resistance alleles within full-sibling families, thereby controlling for the potentially confounding effects of family. This study revealed a codominant pattern of resistance/susceptibility to A. salmonicida infection.…”
Section: Evolutionary Ecology Of the Mhcmentioning
confidence: 99%
“…Allelic diversity will be maintained if different MHC alleles give protection against different parasites, and the composition of the parasite community varies on a temporal and/or spatial scale (Hedrick 2002). Direct associations between certain MHC alleles and resistance to specific diseases have been found in several studies on humans, on chickens (Gallus gallus domesticus), in mouse (Mus musculus) strains (Briles et al 1977;Hormaeche et al 1985;Nauciel et al 1988;Hill et al 1991;Plachy et al 1992;Hill 2001), in studies from a hatchery population of Atlantic salmon (Salmo salar; Langefors et al 2001;Lohm et al 2002) and in an unmanaged Soay sheep (Ovis aries) population (Paterson et al 1998). To our knowledge, however, there are no studies of specific MHC alleles and disease resistance in strictly natural and free-ranging avian populations.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative approach to discriminate advantageous alleles from disadvantageous alleles is to investigate the fitness consequences of the parasite strain (e.g. malaria) in terms of host survival rates [28][29][30]. If a mortality cost for infection during the acute stage can be shown in the population, then a positive association between prevalence of infection and the immunoallele would be interpreted as quantitative disease resistance.…”
Section: Introductionmentioning
confidence: 99%